Literature Review: Effectiveness of Applying the STEAM Method in Training Students' Creative Thinking in High School Physics Learning - Khofifatur Risma Faradillah; Cahyo Febri Wijaksono (Universitas Negeri Surabaya, 2025)
Objective: This research aims to determine the effectiveness of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach in enhancing high school students’ creative thinking skills within the context of physics learning. The study addresses the need for innovative learning strategies to foster creativity, problem-solving, and interdisciplinary integration in science education. Method: The study employed a systematic literature review method. A total of 20 articles published between 2019 and 2024 were selected from national and international journals indexed in Sinta, Scopus, and DOAJ. The selected articles met the criteria of being relevant to STEAM implementation in high school physics learning and its effect on students’ creative thinking skills. The data were analyzed through thematic synthesis to identify patterns, outcomes, and pedagogical strategies. Results: The findings indicate that implementing STEAM in physics education significantly enhances students' creativity. The reviewed studies show that STEAM facilitates active involvement in design, innovation, and interdisciplinary problem-solving. Students demonstrate increased creative thinking, especially in formulating ideas, constructing models, and exploring solutions collaboratively. Novelty: This study synthesizes recent empirical evidence on the effectiveness of STEAM in physics learning, highlighting its role in promoting creativity. The review emphasizes STEAM’s potential as an effective pedagogical alternative to traditional physics instruction, particularly in nurturing 21st-century skills in secondary education.